Comparison of intravitreal antifungal 100 μg voriconazole and 5 μg amphotericin B in experimental Aspergillus flavus endophthalmitis model in rabbits (Faculty of Medicine Universitas Indonesia, 2019)
BACKGROUND Fungal endophthalmitis is a sight-threatening disease associated with high morbidity and Aspergillus sp. is the most common causes. Voriconazole (VCZ) and Amphotericin B (AmB) are the most used antifungal drugs, while head-to-head comparison for in vivo intravitreal efficacy is still unknown. This study was aimed to compare the efficacy of both agents against Aspergillus flavus. METHODS A randomized, masked, controlled-experimental study was conducted on 15 albino New Zealand white rabbits. Endophthalmitis was induced by intravitreal inoculation of Aspergillus flavus. Intravitreal injection was given 24 hours post-inoculation, the rabbits were divided into three groups; 100 μg/0.1 ml VCZ intravitreal injection, 5 μg/0.1 ml AmB, and control. Clinical evaluation of corneal opacity, aqueous cells and flare, and vitreous opacity using Yang's method of quantification were performed at day 1, 3, 5, 7, and 10 after treatment. Mycology quantitative analysis and histopathological examination were performed at the final evaluation. RESULTS Clinical evaluation showed improvement of inflammation in the VCZ and AmB treatment groups (Δ score -2.1 [2.8] and -1.0 [3.2]) compared with the control group (Δ score 0.8 [3.1]). Although the VCZ group demonstrated a better clinical response with less inflammation and relatively intact retina structures in the histopathology result. Number of fungal colony was significantly less in AmB group (CFU/0.1 ml, p < 0.05). CONCLUSIONS Favorable clinical improvement was shown in VCZ group compared to AmB group. Intravitreal VCZ showed a better clinical response tendency for Aspergillus flavus-induced endophthalmitis in rabbits.